Pengaruh Pembentukan Dispersi Padat Meloksikam - PVP K-25 terhadap Penetrasi Perkutan dari Sediaan Gel - Sukmadjaya Asyarie; Sasanti Tarini D; Deni Rahmat (Fakultas Farmasi Universitas Pancasila, 2006)
Most drugs are weak acids or bases and have a low water solubility. Ionized molecules are generally in small amounts absorbed by biological membranes. One possibility of drug modification for transport through biological membranes is by solid disperse system which enhances drug solubility. The solubility of drugs in such a system increases due to particle size reduction and transformation of its crystalline form. In this study, the dispersion system was used to increase the solubility of meloxicam which can influence the percutaneous permeation. Solid dispersion was prepared by modified solvent method using various ratios of PVP K-25 and was also able to lower the meloxicam melting point. Solid dispersion of meloxicam-PVP-K-25 (1:5) was characterized by infrared absorption spectroscopy, differential scanning calorimetry, X-ray diffraction analysis, and thin layer chromatography. Percutaneous penetration was studied by using a flow-through diffusion cell system, and besides that showed a lower diffusion rate of solid dispersion of meloxicam-PVP-K-25 compared to meloxicam.